Supporting Our Lifelong Engagement: Mothers and Teens Exercising (SOLE MATES); a feasibility trial. Issue 6 (2nd July 2020) - Corr, Méabh; McMullen, Jaimie; Morgan, Philip J.; Barnes, Alyce; Murtagh, Elaine M.
ABSTRACT: This study aimed to examine the feasibility of the Supporting Our Lifelong Engagement; Mothers and Teens Exercising ( SOLE MATES ) program. SOLE MATES, a single-arm six-week feasibility trial, comprised six face-to-face sessions. Participants were mothers (n = 27) with daughters (n = 31) aged 12–16 years. Data were collected in Ireland between January 2018 and March 2018. Feasibility benchmarks examined recruitment, data collection, acceptability, resources and participant responses. The primary outcome was daughters' step counts, measured via sealed pedometer for seven consecutive days at baseline and six weeks. Secondary outcomes included mothers' step counts, measures of communication, co-participation in activity, health-related quality of life and parenting practices. Feasibility benchmarks were reached or exceeded, except for retention. Eligibility rates were 93.4%, and baseline activity levels were low. Program content, measures and facilitators were acceptable, demonstrated through a mean score of 4.14 (SD 0.3) on a 5-point Likert Scale. Daily steps increased in mothers (2, 875 increase, p = .009) and daughters (1, 393 increase, p = .007). Positive feasibility metrics demonstrated the program's appeal. Participant responses for outcome measures also indicated program success. However, the relatively homogenous sample and relatively poor initial participation rate were study limitations. The intervention should be evaluated in a randomized controlled trial.